Minimizing synchronization error in compressed domain watermarking - Dutta T.; Soni A.; Gupta H.P. (My University, 2025)
The compressed domain video watermarking has been less expensive since complete decoding and then re-encoding is not required for watermark embedding. Handling synchronization error due to embedding is a challenging task, especially, due to motion compensation. In this paper, we propose an embedding scheme that can minimize desynchronization in the watermark extraction process at the decoder for embedding in compressed videos with better visual quality. Experimental results show the effectiveness of the proposed scheme. © Springer Nature Singapore Pte Ltd. 2020.